2022
DOI: 10.3390/agronomy12081949
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Diversity of Turnip-Rooted Parsley Cultivars

Abstract: The quality of turnip-rooted parsley (Petroselinum crispum var. tuberosum) as a seasoning ingredient depends on the content and composition of the essential oil. The content of essential oil is influenced by many factors, the main of which are genetic variations and environmental conditions. The presented work presents for the first time a comparison of such numerous cultivars of root parsley in terms of the essential oil content in both the roots and the leaves. The experiment compared the content and composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Studies conducted to determine essential oil content have shown that essential oil yield is between 0.08-9.63%. Differences in essential oil yield and composition may have occurred depending on geographical conditions, collection season, and methods used for extraction [27].…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…Studies conducted to determine essential oil content have shown that essential oil yield is between 0.08-9.63%. Differences in essential oil yield and composition may have occurred depending on geographical conditions, collection season, and methods used for extraction [27].…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…In spice production, attention is given to high-yielding varieties and those characterized by aroma stability. Gruszecki and Walasek-Janusz [20] evaluated the yield, content, and chemical composition of EOs of 15 turnip-rooted parsley [Petroselinum crispum (Mill.) Nym.…”
Section: Yield and Quality Of Aromatic Plantmentioning
confidence: 99%
“…In the assimilatory organs, the composition of the oils was more varied, indicating a more active and individual adaptation of the plants to changing conditions during the different growing seasons. Root parsley is mainly cultivated for its aromatic roots; the above studies [20] show that its leaves are a full-flavored spice and contain many EOs. Furthermore, the varied response of varieties, depending on weather conditions, regardingthe content of EOs may indicate the possibility of selecting varieties suitable for crop weather conditions.…”
Section: Yield and Quality Of Aromatic Plantmentioning
confidence: 99%
“…Petroselinum crispum (Mill) Fuss is a perennial herb ( Figure 1 ), native to the Mediterranean region and used in the food, cosmetic, and pharmaceutical industries for its aromatic properties; it is commonly known as parsley and belongs to the Apiacea family [ 14 ]. It has been introduced and cultivated in many parts of the world due to its medicinal effects such as: antiseptic, stimulant, emmenagogue, antispasmodic, carminative, and stomachic effects, and its action on the uterine fiber [ 15 , 16 , 17 ]. On the other hand, the EO of P. crispum presents a high content of apiol [ 18 ], myrcene, 1,3,8-p-menthatriene, myristicin, β-phellandrene, and other terpenoids [ 19 ].…”
Section: Introductionmentioning
confidence: 99%